Epigenetic Biomarkers in Head and Neck Cancer - Shilpi, Gupta; Prabhat, Kumar; Jayant, Maini; Harsimrut, Kaur; Bhudev, C. Das (Journal of Cancer Genetics And Biomarkers, 2018)
Head and neck cancers (HNCs) are the most prevalent and aggressive type of cancers. Genetic, epigenetic, environmental and viral risk-factors are associated with HNC carcinogenesis. Persistent infection of oncogenic human papillomaviruses (HR-HPVs) represent distinct biological, molecular and epigenetic entities in HNCs. There are three main epigenetic mechanisms that regulate transcription, these are DNA methylation, histone modifications and alteration in non-coding RNA networks, which can dissected to identify innovative and accurate epigenetic biomarkers for diagnosis and prognosis of HNC patients. Due to the lacunae of accurate distinctive biomarkers for the definite diagnosis of HNC, the identification of predictive epigenetic markers is necessary that might modify or increase HNC patient’s survival. In this mini review, we briefly summarize the current knowledge of different epigenetic biomarkers in HNC.
Keywords: Head and neck cancer; HPV; Epigenetic biomarker; DNA methylation; Chromatin remodelers; Histone protein modification & non-coding RNAs.